2021
DOI: 10.1007/s43032-021-00464-y
|View full text |Cite
|
Sign up to set email alerts
|

Placental Mitochondrial Abnormalities in Preeclampsia

Abstract: Preeclampsia complicates 5–8% of all pregnancies worldwide, and although its pathophysiology remains obscure, placental oxidative stress and mitochondrial abnormalities are considered to play a key role. Mitochondrial abnormalities in preeclamptic placentae have been described, but the extent to which mitochondrial content and the molecular pathways controlling this (mitochondrial biogenesis and mitophagy) are affected in preeclamptic placentae is unknown. Therefore, in preeclamptic (n = 12) and control (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 56 publications
2
56
0
1
Order By: Relevance
“…Though not yet utilized in the clinic, routinely measuring vasopressin during pregnancy is a promising avenue for predicting the future development of preeclampsia and providing more proactive care in these patients [ 171 ]. In terms of molecular targets, less explored areas include the modulation of RGS proteins to mitigate the negative effects of excessive GPCR induction via hormones such as angiotensin II, endothelin-1, and vasopressin [ 213 , 263 ] or the alleviation of cellular stress that leads to mitochondrial dysfunction, cell death, circulating DNA, and subsequent TLR9 activation [ 79 , 83 , 244 , 247 , 252 , 264 , 265 , 266 ]. Though much remains undiscovered, translational research [ 152 , 153 , 154 ], basic animal models [ 155 , 213 , 215 ], and mechanistic cell work [ 56 , 57 , 150 , 213 ] have made a profound impact in the field thus far, and emerging technologies such as trophoblast organoid cultures [ 267 ] provide great potential for new insight.…”
Section: Discussionmentioning
confidence: 99%
“…Though not yet utilized in the clinic, routinely measuring vasopressin during pregnancy is a promising avenue for predicting the future development of preeclampsia and providing more proactive care in these patients [ 171 ]. In terms of molecular targets, less explored areas include the modulation of RGS proteins to mitigate the negative effects of excessive GPCR induction via hormones such as angiotensin II, endothelin-1, and vasopressin [ 213 , 263 ] or the alleviation of cellular stress that leads to mitochondrial dysfunction, cell death, circulating DNA, and subsequent TLR9 activation [ 79 , 83 , 244 , 247 , 252 , 264 , 265 , 266 ]. Though much remains undiscovered, translational research [ 152 , 153 , 154 ], basic animal models [ 155 , 213 , 215 ], and mechanistic cell work [ 56 , 57 , 150 , 213 ] have made a profound impact in the field thus far, and emerging technologies such as trophoblast organoid cultures [ 267 ] provide great potential for new insight.…”
Section: Discussionmentioning
confidence: 99%
“…Placental ischemia with OS may aggravate the placental dysfunction and stimulate the placental release of anti-angiogenic mediators. These mediators eventually cause endothelial dysfunction not only in the placenta but also in the kidney with vasoconstriction and hypertension [8,12,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…PE is a multifactorial disease that develops after 20 weeks of gestation and although the underlying pathophysiology is not clear, abnormal placentation has been suggested. The shallow trophoblast migration towards the uterine spiral arterioles and the impaired remodeling of these arteries leads to a hypoperfused placenta, thus creating a favorable environment for developing hypoxia and oxidative stress (OS) [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown decreased protein levels of PGC-1α in PE patients compared with controls (53,55,57), and the transcriptional level of PGC-1α was reduced in pre-term PE and pre-term controls (53) but was not altered between pre-term PE relative to term counterparts (57). All the current studies only assessed the mRNA or protein level of PGC-1α; however, activated PGC-1α (i.e., phosphorylated or deacetylated PGC-1α) has never been reported, and the expression of PGC-1α was not specified in the cytoplasm or mitochondrion.…”
Section: Mitochondria Biogenesismentioning
confidence: 99%